2015
DOI: 10.3233/bme-151301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface roughness on the initial response of MC3T3-E1 cells cultured on polished titanium alloy

Abstract: Abstract. Surface roughness has been considered as an important influencing factor for cell response. The aim of this study was to find out whether MC3T3-E1 cells, a mouse osteoblast-like cell line, can sense the amplitudes of surface topography of titanium alloy (Ti6Al4V), and if surface-dependent cell morphology would be presented on the substrata with varied roughness. A series of polished samples (R a : 0.30~1.80 µm) were prepared to produce macroscopically parallel grooves using different grades of silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 25 publications
3
34
0
6
Order By: Relevance
“…The uncoated Ti6Al4V control discs were smooth with an Ra value of 0.358 ± 0.011 lm, and in agreement with previous reports for Grade 5 titanium alloy implants (0.30-0.50 lm, Wu et al, 2015). Although the chemistry and the nanotopography of the disc surfaces changed as a result of the anodisation and silver plating processes (Figure 1), the surface roughness values were no different to the uncoated controls (Table 1).…”
Section: Antibiofilm Activity and Surface Roughnesssupporting
confidence: 90%
“…The uncoated Ti6Al4V control discs were smooth with an Ra value of 0.358 ± 0.011 lm, and in agreement with previous reports for Grade 5 titanium alloy implants (0.30-0.50 lm, Wu et al, 2015). Although the chemistry and the nanotopography of the disc surfaces changed as a result of the anodisation and silver plating processes (Figure 1), the surface roughness values were no different to the uncoated controls (Table 1).…”
Section: Antibiofilm Activity and Surface Roughnesssupporting
confidence: 90%
“…It has been proven that cellular behavior, such as spreading, adhesion, diffusion, and proliferation, is strongly influenced by some effective factors including roughness, hydrophilicity, morphology, and chemistry of the biomaterial surface. Surface wettability has been reported to have a significant effect on primary cell adhesion . Figure shows that the cell growth on the films increased from 12 to 72 h of incubation.…”
Section: Resultsmentioning
confidence: 93%
“…Noteworthy, previously it has been shown that osteoblast morphology and alignment can also be affected by topographical characteristics of the substrate, particularly when these features exhibit similar dimensions as the cellular microenvironment. 47,48 However, since no differences in cell morphology were observed between cells grown on Ti-static and PS-static for 24 hours (Fig. 6A), the changes in cell morphology and alignment were likely affected by the fluid flow, rather than due to contact guidance by the biomaterial surface.…”
Section: Biomaterials Science Papermentioning
confidence: 94%